Expression of the matrix receptor CD44v5 on chondrocytes changes with osteoarthritis: an experimental investigation in the rabbit. Issue 1 (12th December 2005) - Tibesku, C O; Szuwart, T; Ocken, S A; Skwara, A; Fuchs, S
Abstract : Objective: To evaluate the expression of CD44v5 on chondrocytes of hyaline cartilage during the course of osteoarthritis (OA). Methods: In 12 white New Zealand rabbits the anterior cruciate ligament (ACL) was resected to create an anterior instability of the knee. In 12 control rabbits only a sham operation without resection of the ACL was done. Four animals of each group were killed at 3, 6, and 12 weeks. The loadbearing area was evaluated histologically according to Mankin and by immunostaining for CD44v5. Results: In the trial group, histological grades of OA showed a positive linear correlation with the time after surgery. Immunostaining showed an increased expression of CD44v5 in the control group after 3 and 6 weeks, which dropped to normal after 12 weeks. There was no difference between control and trial groups after 3 and 6 weeks, but a difference was seen after 12 weeks. A significant positive correlation between CD44v5 expression and the histological grade of OA was found ( r  = 0.314). Conclusions: An in vivo increase of expression of the hyaluronan receptor CD44v5 occurs during the course of OA. Further studies are needed to evaluate whether this pattern applies to man and whether new treatment approaches might evolve from this knowledge.